An ecological study of a constructed treatment wetland on a commercial crocodile farm next to the Okavango delta, Botswana - Le Roux, J. C. (University of the Free State, 2020)
Constructed treatment wetlands (CTWs) are hidden weapons for improving water quality of which we have not yet discovered the full potential. The study area was based on a CTW treating the wastewater of Krokovango – a commercial crocodile farm in the village of Samochima next to the Panhandle of the Okavango River, Botswana. The Krokovango CTW cannot specifically be classified as a true CTW, since it does not fit into any of the existing criteria used. This wetland can rather be referred to as a simplified vertical surface flow wetland with no outflow, which is a unique scenario. The aim of the study was to contribute to our general understanding of constructed wetland functioning and, more importantly, the role that planktonic organisms play within these wetlands to improve water quality. Secondly, the study attempted to highlight the potential of simple wastewater treatment systems to show that more expensive or complex systems are not necessarily the only option to be considered for water quality improvement, especially in developing and arid countries such as Botswana. The study took place during July-August 2017, with a follow-up study during June-July 2018. Results from the Krokovango wetland showed that planktonic community comprised of five taxa with a total of 50 species sampled and identified. These organisms depend on each other for survival by maintaining balanced community structures and ultimately ensuring ecosystems remain as natural as possible. Interactions within the trophic structure of wetlands improve water quality and degrade pollutants. Phytoplankton, for example Anabaena sp. (cyanobacteria) and Nitzschia sp. (diatom), form the base of aquatic food webs as the primary producers. Protozoans, for example Paramecium sp., occupy a wide range of trophic levels. Rotifers, such as Brachionus spp. and Platyias patulus, are primarily omnivorous and commonly feed on dead or decomposing organic material, making wheel animalcules critical role players in organically rich water bodies, like the Krokovango CTW. Cladocerans (e.g. Alona affinis) and copepods (e.g. Thermocyclops neglectus) create a trophic link between primary producers and bigger predators. Examples of species mentioned above were also the most abundant within each taxon collected from the Krokovango wetland. Microorganisms in association with wetland vegetation contributed substantially to nutrient cycling and energy flow Physical water quality parameters were measured, and results indicated that total dissolved oxygen, conductivity, temperature, and pH levels of the Krokovango CTW falls in the range of the Okavango River. The Krokovango CTW has been in operation since 2012 and has become an additional habitat for a variety of bird species. The diversity of microinvertebrates, as well as other invertebrates and bird species recorded and identified, is a valuable indication of the wetland’s success as a constructed treatment facility.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2020
Keywords: Krokovango constructed treatment wetland; Biological indicator species; Phytoplankton; Protozoa; Rotifera; Cladocera; Copepoda; Water quality